2016
DOI: 10.4000/belgeo.17889
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the influence of the Camp de Tarragona high-speed rail station on first-time and repeat tourists visiting a coastal destination

Abstract: Measuring the influence of the Camp de Tarragona high-speed rail station on first-time and repeat tourists visiting a coastal destination

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…The analyses carried out in Madrid (Pagliara et al, 2015b) and in Naples (Pagliara, 2014) show the same results. Other recent studies analyse the impact of HSR on coastal destinations in Costa Daurada and show that some tourists would not have reached the destination without the presence of an HSR service (Saladié et al, 2016).…”
mentioning
confidence: 99%
“…The analyses carried out in Madrid (Pagliara et al, 2015b) and in Naples (Pagliara, 2014) show the same results. Other recent studies analyse the impact of HSR on coastal destinations in Costa Daurada and show that some tourists would not have reached the destination without the presence of an HSR service (Saladié et al, 2016).…”
mentioning
confidence: 99%
“…The case of the Camp de Tarragona HSR station is a clear example of how station-to-station travel time might not be the most important variable for travellers, since the station's isolated location reduces its attractiveness for tourists travelling for leisure to coastal destinations at Costa Daurada. Furthermore, previous studies have demonstrated that this station has gained a moderate capacity to attract tourists who might otherwise use other modes of transport [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The data used in this study were therefore based on the answers provided by these 545 tourists plus those relating to the transfer distance, time and cost of the trips from the station to the final destinations. This survey had previously been used for other studies measuring the influence of the station on destination choice [30], and also segmenting this influence between first-time and repeat tourists [31] and according to the different points of origin of the passengers [32].…”
Section: Traveller Surveymentioning
confidence: 99%
“…The combined answers to those two questions allowed us to measure the influence of Camp de Tarragona Station on tourists' decisions to visit the Costa Daurada. We used a causal probabilistic method developed by Young et al (2005) and adapted by Saladié et al (2016). The existence of a HSR station near a tourist destination might have justified visiting the destination, though not necessarily be linked to any individual decision to visit the particular destination given the various modes of transportation available.…”
Section: Camp De Tarragona Hsr Station Is An Intermediate Node On Thementioning
confidence: 99%